Hierarchies of evidence applied to lifestyle Medicine (HEALM): introduction of a strength-of-evidence approach based on a methodological systematic review. - Katz, D. L.; Karlsen, M. C.; Chung, M..; Shams-White, M. M.; Green, L. W.; Fielding, J..; Saito, A..; Willett, W.. (Tufts University. Tisch Library., 2019)
Background: Current methods for assessing strength of evidence prioritize the contributions of randomized controlled trials (RCTs). The objective of this study was to characterize strength of evidence (SOE) tools in recent use, identify their application to lifestyle interventions for improved longevity, vitality, or successful aging, and to assess implications of the findings.; Keywords: Strength of evidence, SOE, Systematic review, Lifestyle medicine, Lifetime effects, HEALM.; Springer Open.